The AWESCORE, a patient-reported outcome measure: development, feasibility, reliability, validity and responsiveness for adults with cystic fibrosis. Issue 3 (20th September 2021) - Button, Brenda M.; Wilson, Lisa M.; Burge, Angela T.; Kimmel, Lara; Finlayson, Felicity; Williams, Elyssa; Talbot, Anthony; Tierney, Audrey; King, Susannah; Holland, Anne E.; Keating, Dominic; Kotsimbos, Tom; et al.
Background: Quality of life has improved dramatically over the past two decades in people with cystic fibrosis (CF). Quantification has been enabled by patient-reported outcome measures (PROMs); however, many are lengthy and can be challenging to use in routine clinical practice. We propose a short-form PROM that correlates well with established quality-of-life measures. Methods: We evaluated the utility of a 10-item score (AWESCORE) by measuring reliability, validity and responsiveness in adults with CF. The questions were developed by thematic analysis of survey questions to patients in a single adult CF centre. Each question was scored using a numerical rating scale 0 to 10. Total scores ranged from 0 to 100. Test–retest reliability was assessed over 24 h. To determine validity, comparisons were sought between stable subjects and those in pulmonary exacerbation, and between AWESCORE and Cystic Fibrosis Questionnaire – Revised (CFQ-R). Responsiveness to pulmonary exacerbation in individual subjects was evaluated. Results: Five domains, each with two questions, were identified for respiratory, physical, nutritional, psychological and general health. A total of 246 consecutive adults attending the outpatient clinic completed the AWESCORE. Scores were higher during clinical stability compared to pulmonary exacerbation (mean±sd): 73±11 versus 48±11 (p<0.001). Each domain scored worse during an acute exacerbation (p<0.001). No differences in reliability were observed in scores on retesting using Bland–Altman comparison. The CFQ-R scores (mean±sd : 813±125) and AWESCORE (81±13) were moderately correlated (Pearson's r=0.649; p=0.002). Conclusions: The AWESCORE is valid, reliable and responsive to altered health status in CF. The AWESCORE: a new, short patient-reported outcome measure for adults with cystic fibrosis in clinical settings. It is feasible, valid, reliable and responsive to change, and developed to enhance communication and decision-making in clinical practice. https://bit.ly/2TWDaj3